2019
DOI: 10.3390/nu11051058
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Sweetened Beverages Contribute Significantly to College Students’ Daily Caloric Intake in Jordan: Soft Drinks Are Not the Major Contributor

Abstract: Sugar sweetened beverages (SSBs) are caloric-dense and associated with poor diet quality which may result in weight gain and obesity. Obesity is an independent risk factor for several chronic diseases. This study aimed to (1) assess the consumption level of SSBs among college students in Jordan and (2) examine the relationship of consumption level to body weight. The current study is a cross-sectional study conducted on 967 college students (55.3% males and 44.7% females). Consumption of SSBs was assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 54 publications
3
28
1
2
Order By: Relevance
“…The results of our study indicate that males consume more soda and energy drinks compared to females. Similarly, a recent cross-sectional study among college students in Jordan revealed that male students consumed significantly more calories from sugar-sweetened beverages compared to female students [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study indicate that males consume more soda and energy drinks compared to females. Similarly, a recent cross-sectional study among college students in Jordan revealed that male students consumed significantly more calories from sugar-sweetened beverages compared to female students [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] Specifically, on college campuses, sugar-sweetened beverages are heavily promoted through advertisements and promotional campaigns. [ 41 42 43 ] Some of the most heavily promoted drinks, such as sports drinks, could be perceived as healthy drink options, despite their high content of added sugars. [ 43 44 ] Understanding that these seemingly “healthy” products contain high amounts of added sugar requires young adults to have CNL, so that they may be less influenced by marketing techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Poor sleep has been linked to increased appetites and the desire to choose sugary foods [9]. Sugar-sweetened beverage consumption represents a significant source of energy consumption in college students that may contribute to weight gain, obesity and other negative health outcomes [10,11]. Pathways through which lack of sleep might adversely effect energy balance and lead to weight gain include factors such as alterations in appetite and glucose regulation, increased food intake, and reduced energy expenditure [12].…”
Section: Introductionmentioning
confidence: 99%